Case Report: Metastatic Bronchopulmonary Carcinoid Tumor to the Pineal Region - Cuoco, Joshua A.; Kortz, Michael W.; McCray, Edwin; Guilliams, Evin L.; Busch, Christopher M.; Rogers, Cara M.; Jarrett, Robert W.; Mittal, Sandeep (Frontiers in Endocrinology, 2021)
Intracranial spread of a systemic malignancy is common in advanced staged cancers; however, metastasis specifically to the pineal gland is a relatively rare occurrence. A number of primary lesions have been reported to metastasize to the pineal gland, the most common of which is lung. However, metastasis of a bronchial neuroendocrine tumor to the pineal gland is a seldom-reported entity. Here, we present a 53 year-old female who presented with worsening headaches and drowsiness. MRI brain revealed a heterogeneously enhancing partially cystic mass in the pineal region. The patient had an extensive oncologic history consisting of remote stage IIA invasive breast ductal carcinoma as well as a more recently diagnosed atypical bronchopulmonary neuroendocrine tumor with lymph node metastases. She underwent microsurgical volumetric resection of the large pineal mass and a gross total removal of the tumor was achieved. Histopathology confirmed a metastatic tumor of neuroendocrine origin and the immunohistochemical profile was identical to the primary bronchopulmonary carcinoid tumor. Eight weeks after surgery, she underwent stereotactic radiosurgical treatment to the resection cavity. At one-year follow-up, the patient remains clinically stable without any new focal neurological deficits and without any evidence of residual or recurrent disease on postoperative MRI. Metastatic neuroendocrine tumors should be considered in the differential diagnosis of pineal region tumors and aggressive surgical resection should be considered in selected patients. Gross total tumor resection may afford excellent local disease control. We discuss the relevant literature on neuroendocrine tumors and current treatment strategies for intracranial metastases of neuroendocrine origin.